Comparative study of inhibitory potential of dietary phytochemicals against quorum sensing activity of and biofilm formation by Chromobacterium violaceum 12472, and swimming and swarming behaviour of Pseudomonas aeruginosa PAO1 - Bali, Elif Burcu (Array, 2019)
Quorum sensing (QS) and biofilm formation are important mechanisms related to antibiotic resistance of many pathogens. Alternative treatments are needed to prevent recurrent or chronic infections caused by multi-resistant pathogens. Therefore, the aim of this study is to investigate and compare the inhibitory potential of the dietary phytochemicals: curcumin, quercetin, apigenin, pyrogallol, gallic acid and luteolin against QS of and biofilm formation by Chromobacterium violaceum ATCC 12472 and the swimming and swarming abilities of Pseudomonas aeruginosa PAO1. Anti-QS potential of the phytochemicals was evaluated qualitatively and quantitatively using C. violaceum via the disk diffusion assay based on violacein pigment inhibition at the subminimal inhibitory concentrations ranging from 46.87 to 750 µg/mL. The results of anti-QS and antibiofilm activities on C. violaceum demonstrated that all the phytochemicals except pyrogallol and gallic acid inhibited violacein production (from (11.0±0.1) to (88.2±0.1) %) in a concentration-dependent manner.